Mesenteric lymphadenitis caused by Yersinia enterocolitica - Zińczuk, Justyna; Wojskowicz, Piotr; Kiśluk, Joanna; Fil, Dawid; Kemona, Andrzej; Dadan, Jacek (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Yersiniosis is an acute or chronic, zoonotic disease caused by infection of Gram-negative rods Yersinia enterocolitica . It can be transmitted by the consumption of originally contaminated food products (pork, unpasteurized milk) or secondarily contaminated with animal or vegetable products. The clinical picture of infection may have a variable course is related to the age and physical condition of the patient, or pathogenic properties of microorganisms. Infection caused by Y. enterocolitica can occur in different clinical forms: food poisoning, colitis, mesentric lymphadenitis, erythema nodosum, arthritis, pharyngitis, pneumonia, meningitis, sepsis. The aim of this study was to present a rare case of infection with Y. enterocolitica mesenteric lymph nodes coexistent with appendicitis.